Digital Marketing Strategies To Increase Hotel Room Sales In The Technology 4.0 Era At Hotel Mercure Bandung Centre - Prayoga, Kokoh; Insani, Siti (JAKI : Jurnal Akuntansi, 2025)
Digital marketing in the era of Technology 4.0 plays a crucial role in the hospitality industry, particularly in increasing hotel room sales. Hotel companies are increasingly relying on digital marketing strategies to achieve competitive advantage in an increasingly competitive market. Mercure Bandung City Centre Hotel is a company engaged in providing services and accommodation. This study aims to explore how the implementation of digital marketing by the marketing department of Puri Asri Hotel can help generate competitive advantage, with a focus on the communication aspect through digital marketing communications. This study explores the most effective digital marketing strategies to increase hotel room sales through the use of various digital platforms such as social media, SEO, and content-based marketing. The results show that hotels that implement appropriate digital marketing strategies can increase online visibility, attract new customers, and optimize room booking conversions. In addition, the use of advanced technologies such as data analytics and AI for marketing personalization also significantly influences sales success. Digital marketing is a key strategy used by hotels to reach consumers more widely, quickly, and precisely. This study aims to identify and analyze the most effective digital marketing strategies in increasing hotel room sales in the era of Technology 4.0. The approach used is qualitative-descriptive with case studies of several star-rated hotels that have actively implemented digital strategies. Therefore, the Mercure Bandung City Centre Hotel must improve its digital marketing strategy in the era of technology 4.0 on digital platforms to be able to compete in the hospitality industry and increase room sales at the Mercure Bandung City Centre Hotel. This research provides a new contribution in understanding how technology 4.0 supports marketing transformation in the hospitality industry, especially at the Mercure Bandung City Centre Hotel.